The Girls of Riyadh (Analisis Sastra Islam) (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
Islamic literature has been recognized by the readers of literature in the world, both in the Arab countries as well as countries of non-Arab, especially the Western world and the Islamic world in general. Introduction to readers of literature in Islamic literature, especially the works of Arabic literature who breathe Islam, can be seen in poems (Qasidah) and the famous Arabic novel, even entered in the category of masterpiece, for example, among other things, the Qasidah Burdah and the story of Alfun Laylah wa Laylah. both of the Arab-Islamic literature has many inspired the birth of world literature that gets reception and remarkable appreciation of readers in the world literature. Novel The Girl of Riyadh has elements that exist in Islamic literature, which can be used as a first step to investigate those later authors can refer to it as Islamic literature. The Girls of Riyadh highlighted the problems faced by Muslim women in Saudi Arabia.